4 - L’institutionnalisation des délibérations dans l’espace public au sein des chefferies Bamileke de l’Ouest-Cameroun: https://doi.org/10.4314/ad.v34i3-4.63528 - Tchoupie André (Africa Development, 2009)
Based on the different variances of neo-institutionalism, this paper at- tempts to analyse the process through which public space deliberation is becoming a real institution in the Bamileke chieftaincies of Western Cameroon. It demonstrates that far from appearing as a spontaneous generation, public space deliberation represents here instead a reality that socio-political actors are permanently building and rebuilding through their actions and interactions. Following this construction, public sphere deliberative practice followed a trajectory mainly leading to its being erected as one of the main characteristics of the Bamileke culture. This has been so thanks to the fact that, it has established itself as a real base on which all political decisions have rested, and has also been undergoing over time constant changes marked by an harmonious combination of acquired traditional values and modernity demand, which helps it face up to the diverse environmental forces tending to weaken its dynamism.